2020
DOI: 10.1371/journal.pone.0234145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cord Blood Serum (CBS) on viability of retinal Müller glial cells under in vitro injury

Abstract: Oxidative stress and inflammation determine retinal ganglion cell degeneration, leading to retinal impairment and vision loss. Mü ller glial cells regulate retinal repair under injury, through gliosis. Meanwhile, reactive gliosis can turn in pathological effects, contributing to neurodegeneration. In the present study, we tested whether Cord Blood Serum (CBS), rich of growth factors, might improve the viability of Mü ller cells under in vitro damage. BDNF, NGF, TGF-α, GDNF and EGF levels were measured in CBS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We next investigated the gene expression of CD31 and GFAP in MIO‐M1/HUVEC coculture at p4 and p8 under oxidative stress conditions. Based on cell viability data and on our previous findings (Ciavarella et al, 2020), H 2 O 2 was used at 500 μM for 24 h. We observed up‐regulation of CD31 mRNA in MIO‐M1/HUVEC coculture exposed to H 2 O 2 in comparison to untreated controls (30‐fold increase in MIO‐M1/HUVEC p4, p 0.076; 100‐fold increase in MIO‐M1/HUVEC p8, p = 0.033, unpaired t test) (Figure 8a), suggesting a potential modulation of cell damage through the stimulation of the endothelial differentiation and neo‐vascularization. However, the low expression of GFAP transcript indicated that this response was not accompanied by MIO‐M1 activation and cell suffering (Figure 8b).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We next investigated the gene expression of CD31 and GFAP in MIO‐M1/HUVEC coculture at p4 and p8 under oxidative stress conditions. Based on cell viability data and on our previous findings (Ciavarella et al, 2020), H 2 O 2 was used at 500 μM for 24 h. We observed up‐regulation of CD31 mRNA in MIO‐M1/HUVEC coculture exposed to H 2 O 2 in comparison to untreated controls (30‐fold increase in MIO‐M1/HUVEC p4, p 0.076; 100‐fold increase in MIO‐M1/HUVEC p8, p = 0.033, unpaired t test) (Figure 8a), suggesting a potential modulation of cell damage through the stimulation of the endothelial differentiation and neo‐vascularization. However, the low expression of GFAP transcript indicated that this response was not accompanied by MIO‐M1 activation and cell suffering (Figure 8b).…”
Section: Resultsmentioning
confidence: 96%
“…We next investigated the gene expression of CD31 and GFAP in MIO-M1/HUVEC coculture at p4 and p8 under oxidative stress conditions. Based on cell viability data and on our previous findings(Ciavarella et al, 2020), H 2 O 2 was used at 500 μM for 24 h. We observed up-regulation of CD31 mRNA in MIO-M1/HUVEC coculture exposed to H 2 O 2 in comparison to untreated controls (30-fold increase in MIO-M1/HUVEC p4, p 0.076; 100-fold increase in MIO-M1/HUVEC p8, p = 0.033, unpaired t test)…”
mentioning
confidence: 99%
“…Previous research showed the efficacy of cord blood serum (CB-S) at ameliorating the effects of oxidative stress and inflammation on the viability of rat and human Muller cells [27] by modulating the state of activation which typically occurs when glial cells are exposed to tissue damage. In the present study, the effect of lyophilized products from CB as a source was explored in MIO-M1 cells in terms of wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…It is also critical to understand whether EGFR signaling can induce Müller cells to become like A2 astrocytes, as they undergo reactive gliosis along with retinal astrocytes in response to injury. Additionally, there has been increasing attention to the possibility to deliver neurotrophic factors by eye drops, and clinical studies suggest that this could represent a safe and effective strategy for treating retinal degenerative diseases [42,[90][91][92][93][94]. Hence, future research should evaluate the efficacy of EGFR ligand-based eye drops after ONC and investigate whether the topical delivery of EGFR ligands could generate growthsupportive phenotypes of retinal astrocytes and Müller cells.…”
Section: Discussionmentioning
confidence: 99%